IDEAL LIFE PHILOSOPHY REVEALED IN ’BRIHATTRAYAH’ OF SANSKRIT LITERATURE - Patel, Maheshkumar G.; Bariya, Pravinkumar Kalubhai (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The aim of human life is to achieve ’self’ and attain unity with the Supreme Being. To live life in such a way that the values ​​of humanity can be understood and satisfied with it, and to take refuge in the Supreme Being in the end after performing one’s duties. The world is mainly materialistic. To be free from its bonds and to remain diligent in one’s work and to travel in such a way that one can remain absorbed in it, is the success of life. Literature highlights the aspects related to life. And develops the art of living. The seeds of the art of living are found in a refined form in literature. Knowledge of literature arouses the feelings within a person, which awakens the feeling of doing something new in his life and gives self-knowledge.